Functional Suitability Measurement using Goal-Oriented Approach based on ISO/IEC 25010 for Academics Information System - Ajeng Savitri Puspaningrum; Siti Rochimah; Rizky Januar Akbar (Journal of Information Systems Engineering and Business Intelligence, 2017)
Abstract— Rapid of information technology development grow a new competitive environment. Including higher education, they need to improve their service quality in order to provide education service in more competitive. One of the ways of using information technology in higher education is the used of Academic Information System (AIS). AIS was developed to achieve the goals of the learning process which is one of vision and mission organization success factor. The measurement is needed to evaluate the quality of AIS. Functionality is one of the quality factors which is measured by observing the correlation between function and functional suitability. In this study, the quality of AIS functional suitability is measured using goal-oriented approach base on ISO/IEC 25010 in the perspective of a lecturer. The strategic plan of an institution is used as a reference to measure if the system used to have meet institution goals when using this approach. The result shows that the measurement using goal-oriented approach become more objective and suitable to the need of used AIS quality improvement for the institution than the measurement with ISO/IEC 25010 only. Keywords— Academic Information System, Functional Suitability, GQM, ISO/IEC 25010